Aklimatisasi Bakteri Rumen Sapi Pada Pengolahan Palm Oil Mill Effluent - Maulani, Annisa; Andrio, David; Evelyn, Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm oil mill effluent (POME) has high chemical oxygen demand (COD) content of 44.444 mg/L causing the most suitable processing technology is anaerobic digestion. This research aimed to study soluble COD removal efficiency and bacteria growth rate as VSS in acclimatization process of rumen fluid as inoculum addition in POME treatment. Acclimatization I was conducted in circulating bed reactor (CBR) with working volume 20 L, ratio of glucose : POME inside the reactor is 50% : 50% (%v/v). Meanwhile, acclimatization II was conducted in upflow anaerobic sludge blanket (UASB) with working volume 10 L, ratio of glucose : POME inside the reactor is 0% : 100% (%v/v). Acclimatization I and II was done in 20 and 50 days with soluble COD removal efficiency 80,36% and 65,41%, respectively. Meanwhile, bacteria growth rate as VSS has amount of 277 mg/L/day and 429 mg/L/day, respectively.Keywords: palm oil mill effluent, acclimatization, mixed culture bacteria, glucose, soluble COD, VSS